Pavlo Postyshev: political ideologist of research collective farm in the USSR in the 30s years of the XX century - S. D. Kovalenko (History of science and technology, 2018)
Applying the method of historical and scientific analysis, the role of Pavlo Petrovich Postyshev as a political ideologist of a collective farm research in the USSR in the 30s of the XX century has been highlighted. His contribution to the development of research collective farm on the territory of the USSR has been analyzed and presented, in particular as the organizer of the houses-laboratories - new structural units of branch science for the needs of agricultural production in the Soviet village.